Study on Incidence of Metabolic Complications due to Chronic Progesterone Exposure in Canine Pyometra - Revathy, Bhathra Nagaraja Kumar; Vaiyapuri, Prabaharan; Gupta, Chhavi; Shanmugasami, Malmarugan (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
This study was conducted on 20 intact bitches between 2-6 years of age presented to the Veterinary Clinical Complex of the College, Tirunelveli, with the history of anorexia, abdominal enlargement, polyuria and polydipsia. After detailed anamnesis, gynaeco-clinical examination and ultrasonography all animals were diagnosed as having pyometra. Further, bitches were subjected to detailed haemato biochemical analysis, urine analysis and intravenous glucose tolerance test. The haematological disorders encountered were anaemia, haemoconcentration, leucocytosis, thrombocytopenia, neutrophilia and monocytosis. Blood glucose tolerance values recorded were 95.92 ± 0.39 and 285.0 ± 0.72 mg/dL, respectively, at 0 and 60 min of i/v test. Higher serum values of BUN, creatinine, ALT, AST, GGT, ALP, triglyceride, cholesterol, LDH were recorded in majority of cases. These parameters were used as the diagnostic indicators for the incidence of metabolic complications in pyometra such as hepatocellular dysfunction, diabetes mellitus, nephropathy, hyperlipidemia and lactoacidosis, which was recorded in 90, 60, 70, 40 & 50% of affected dogs, respectively. Thus, this study documents the incidence rate of concealed metabolic complications arising mainly due to chronic progesterone exposure in canine pyometra and novel use of haemato-biochemical diagnostic markers to predict the prognosis and recovery rate in canine pyometra.